Do Combinations of Behavior Change Techniques That Occur Frequently in Interventions Reflect Underlying Theory?. Issue 11 (22nd September 2020) - Bohlen, Lauren Connell; Michie, Susan; de Bruin, Marijn; Rothman, Alexander J; Kelly, Michael P; Groarke, Hilary N K; Carey, Rachel N; Hale, Joanna; Johnston, Marie
Abstract: Background: Behavioral interventions typically include multiple behavior change techniques (BCTs). The theory informing the selection of BCTs for an intervention may be stated explicitly or remain unreported, thus impeding the identification of links between theory and behavior change outcomes. Purpose: This study aimed to identify groups of BCTs commonly occurring together in behavior change interventions and examine whether behavior change theories underlying these groups could be identified. Methods: The study involved three phases: (a) a factor analysis to identify groups of co-occurring BCTs from 277 behavior change intervention reports; (b) examining expert consensus ( n = 25) about links between BCT groups and behavioral theories; (c) a comparison of the expert-linked theories with theories explicitly mentioned by authors of the 277 intervention reports. Results: Five groups of co-occurring BCTs (range: 3–13 BCTs per group) were identified through factor analysis. Experts agreed on five links (≥80% of experts), comprising three BCT groups and five behavior change theories. Four of the five BCT group–theory links agreed by experts were also stated by study authors in intervention reports using similar groups of BCTs. Conclusions: It is possible to identify groups of BCTs frequently used together in interventions. Experts made shared inferences about behavior change theory underlying these BCT groups, suggesting that it may be possible to propose a theoretical basis for interventions where authors do not explicitly put forward a theory. These results advance our understanding of theory use in multicomponent interventions and build the evidence base for further understanding theory-based intervention development and evaluation. Abstract : The theory underlying behavior change interventions is important for understanding how and why they work, but may not be made explicit in published reports. This study found that experts in behavior change can agree on some of these theories by looking at the combinations of behaviour change techniques used in these interventions.